Membangun Indonesia Dari Daerah Dengan Penguatan Partisipasi Masyarakat - I Wayan Sutrisna (Jurnal Ilmiah Cakrawarti, 2019)
National development has a multidimensional goal, one of which is to realize a democraticIndonesian society, because with a more democratic condition, it allows the public to be more open toparticipate in development in all fields. The development of faster and more complex developmentdemands all components involved in the development process and democracy able to realize what isthe goal of national development.Community participation in the development process in Indonesia in general is currently very low. Thecommunity is still reluctant to engage in a continuous manner in the entire process of developmentplanning, implementation and evaluation carried out by the government. This low participation is aresult of government policies that are still lacking in providing space for every citizen to participate indevelopment. The implementation of the Development Planning Conference (Musrenbang) starting atthe village level up to the national level is considered by some as merely a serimonial process. Nationaldevelopment based on community empowerment will be realized if the government has a strong desireto implement it. The government encourages and provides opportunities for the public to be involved inthis participatory pattern. This pattern makes the community more empowered and participates inenjoying the cake of economic growth resulting from the development process that is carried out.Quality economic growth makes development carried out by the government together with allcomponents of the nation able to improve the welfare of society at large in accordance with what is thegoal of national development itself. National development balanced with active community participation or empowered communities will produce a force capable of realizing national goalsaccording to their goals. Encouraging community participation in developing Indonesia from theregions will be realized if the government has a good desire to implement it. The government mustencourage and provide opportunities for the public to be involved in this participatory pattern. Thispattern makes the community more empowered and participates in enjoying the cake of economicgrowth resulting from the development process that is carried out